Functionalized quinolizinium-based fluorescent reagents for modification of cysteine-containing peptides and proteins. Issue 10 (22nd February 2022) - Kung, Karen Ka-Yan; Xu, Cai-fung; O, Wa-Yi; Yu, Qiong; Chung, Sai-Fung; Tam, Suet-Ying; Leung, Yun-Chung; Wong, Man-Kin
Abstract : New quinolizinium-based fluorescent reagents were made by visible light-mediated gold-catalyzed cis -difunctionalization of quinolinium diazonium salts and trimethylsilyl alkyne derivatives. Abstract : A series of quinolizinium-based fluorescent reagents were prepared by visible light-mediated gold-catalyzed cis -difunctionalization between quinolinium diazonium salts and electron-deficient alkyne-linked phenylethynyl trimethylsilanes. The electron-deficient alkynyl group of the quinolizinium-based fluorescent reagents underwent nucleophilic addition reaction with the sulfhydryl group on cysteine-containing peptides and proteins. The quinolizinium-based fluorescent reagents were found to function as highly selective reagents for the modification of cysteine-containing peptides and proteins with good to excellent conversions (up to 99%). Moreover, the modified BCArg mutants bearing cationic quinolizinium compounds 1b, 1d, 1e and 1h exhibit comparable activity in enzymatic and cytotoxicity assays to the unmodified one.